An approach to research on coaching and improvement of teaching practices in Latin America - Reséndiz Melgar, Norma Nélida (Avances en Supervisión Educativa, 2021)
This article aims to analyze, from a comparative perspective, the way in which counseling is investigated in different Spanish-speaking countries of Iberoamerica. Initially, the relationship between counseling, educational change and school improvement is exposed, in order to understand the research examined.Subsequently, such investigations are addressed. In these it was identified that the majority are based on a qualitative paradigm and that their main objects of study are the processes and the way in which counseling is carried out, its sustainability over time, and the figure of the advisor (competences, training, etc.).Then, characteristics of the consultancies investigated are exposed, such as their approaches and forms of organization. Finally, it is concluded that counseling, despite the differences between contexts and countries, has accompaniment as its pedagogical core.
Keywords: Educational counseling; Pedagogical counseling; School improvement; School effectiveness; Pedagogical coaching; Basic education